Journal relating to international and home affairs kept by Liam de Róiste, chairman of the Sinn Féin Executive in Cork - De Róiste, Liam, 1882-1959 (1918)
Includes descriptions of Sinn Féin Ard Fheiseanna, references to Tomás MacCurtain, De Valera’s visit to Cork in December 1917, food shortage in Cork, conscription etc.
Keywords: MacCurtain, Tomás, -- 1884-1920; De Valera, Éamon, -- 1882-1975; Sinn Féin; World War, 1914-1918 -- Ireland